PENGARUH LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN LAPANGAN DEPARTEMEN GRASBERG - Quinerita Stevani Aruan; Mahendra Fakhri (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2015)
The competition in business world demands a company to improve its performance. The work environment became a necessity for employees. The company’s eforts in fulflling the needs are the improvement of the physical work environment and the non-physical work environment in the company. PT. Freeport itself has realized that the company’s success depends on the contribution of each employee. In order to do so, Freeport is committed to achieving excellence which includes necessity and satisfaction of each employee.The purpose of this research is to understand the representation of work environment between physical work environment and non-physical work environment, job satisfaction, as well as the infuence of work environment on job satisfaction at Grasberg Power Distribution Department in PT. Freeport Indonesia Tembagapura Papua.Quantitative approach is used simultaneously with causal research method. Number of samples were 57 respondents, where the sampling technique used is saturated sample technique. Descriptive analysis and multiple regression analysis are used as the technique of data analysis. The result of partial hypothesis test showed the physical work environment and the non-physical work environment had the most positive and signifcant infuence to the employees satisfaction with t > t and the signifcant test result was 0,000 smaller count table than 0,05. H was accepted. Based on the result of simultaneous hypothesis test, the work 0 environment (the physical work environment and the non-physical work environment) has the positive signifcant infuence to the employees satisfaction of Grasberg Power Distribution Department. It can be evidenced by F calculate > F table (40,086> 3,170) with the signifcancy at 0,000 < 0,05. According on the determination coefcient test, around 59,8% employees satisfaction variable was afected by the work environment. The residue which are 40,2% was afected by the other variables which is not investigated in this research.Keywords: Physical Work Environment, Non-Physical Work Environment, Employee Satisfaction.